Ozone Applications in Food Industry - Elif Savaş; Hakan Tavşanlı; İlhan Gökgözoğlu (Turkish Journal of Agriculture: Food Science and Technology)
Known as active oxygen Ozone (O3), are among the most effective antimicrobials. The sun's ultraviolet rays and ozone caused by electric arcs of lightning occurring instantly around the world, and is available as a protective shield protects the animals against the effects of the sun's radiation. In the food industry, directly or indirectly in contact with food during processing of foods and chemical treatment of water disinfection bacteriological emerges as an alternative protection method. In this study, the effects of the ozone applications will evaluated as an alternative to conventional disinfectants in food industry.